The Impact of Overconfidence on Capital Structure in Turkey - Serpil Tomak (International Journal of Economics and Financial Issues, 2013)
The aim of this study is to investigate the relationship between the overconfidence and capital structure in Turkish manufacturing firms. In addition to management confidence, the impact of the fundamental factors on the market leverage is analyzed. The annual data of 115 manufacturing firms on the Istanbul Stock Exchange (ISE) for the period between 2002 and 2011 is used for the analysis by means of the ordinary least squares regression model. The results show that the relationship between confidence and leverage is ambiguous. There isn’t enough evidence for the idea of overconfident managers tends to use more debt level. However, this study provides some evidence for firm specific factors like size and profitability effects on leverage.